Coherence of a charge stabilised tin-vacancy spin in diamond - Goerlitz, Johannes; Herrmann, Dennis; Fuchs, Philipp; Iwasaki, Takayuki; Taniguchi, Takashi; Rogalla, Detlef; Hardeman, David; Colard, Pierre-Olivier; Markham, Matthew; Hatano, Mutsuko; Becher, Christoph (npj Quantum Information, 2022)
Quantum information processing (QIP) with solid state spin qubits strongly depends on the efficient initialisation of the qubit’s desired charge state. While the negatively charged tin-vacancy (SnV−) centre in diamond has emerged as an excellent platform for realising QIP protocols due to long spin coherence times at liquid helium temperature and lifetime limited optical transitions, its usefulness is severely limited by termination of the fluorescence under resonant excitation. Here, we unveil the underlying charge cycle, potentially applicable to all group IV-vacancy (G4V) centres, and exploit it to demonstrate highly efficient and rapid initialisation of the desired negative charge state of single SnV centres while preserving long term stable optical resonances. In addition to investigating the optical coherence, we all-optically probe the coherence of the ground state spins by means of coherent population trapping and find a spin dephasing time of 5(1) μs. Furthermore, we demonstrate proof-of-principle single shot spin state readout without the necessity of a magnetic field aligned to the symmetry axis of the defect.
Created from Fastlane, Scopus look-up